Oligometastasis and local ablation in the era of systemic targeted and immunotherapy - Mazzola, Rosario; Jereczek-Fossa, Barbara Alicja; Franceschini, Davide; Tubin, Slavisa; Filippi, Andrea Riccardo; Tolia, Maria; Lancia, Andrea; Minniti, Giuseppe; Corradini, Stefanie; Arcangeli, Stefano; Scorsetti, Marta; Alongi, Filippo (Radiation Oncology, 2020)
Background: During these last years, new agents have dramatically improved the survival of the metastatic patients. Oligometastases represent a continuous field of interest in which the integration of metastases-directed therapy and drugs could further improve the oncologic outcomes. Herein a narrative review is performed regarding the main rationale in combining immunotherapy and target therapies with SBRT looking at the available clinical data in case of oligometastatic NSCLC, Melanoma and Kidney cancer. Material and method: Narrative Review regarding retrospective and prospective studies published between January 2009 to November 2019 with at least 20 patients analyzed. Results: Concerning the combination between SBRT and Immunotherapy, the correct sequence of remains uncertain, and seems to be drug-dependent. The optimal patients' selection is crucial to expect substantial benefits to SBRT/Immunotherapy combination and, among several factors. A potential field of interest is represented by the so-called oligoprogressed disease, in which SBRT could improve the long-term efficacy of the existing target therapy. Conclusions: A low tumor burden seems to be the most relevant, thus making the oligometastatic disease represent the ideal setting for the use of combination therapies with immunological drugs.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Immunotherapy; Metastases-directed therapy; Oligometastasis; Target therapy